Gallos de pelea: algunas precisiones desde el diálogo con un gallero - Rodríguez, Onésimo (2014)
The following article arises from an ongoing research project entitled “‘Dying cock good!’ Young, cockpits and cockfighting” developed from the School of Anthropology at La Universidad de Costa Rica. This paper attempts to explore some of the realities experienced by a young cocker (referring to the dynamics related to breeding and cockfighting) narrated from his own orality, ie argumentative exposition of the evidence is from a dialogical perspective that enables observe the reflection and analysis of the subject of extensive way.